2021
DOI: 10.1039/d0ra09754c
|View full text |Cite
|
Sign up to set email alerts
|

Direct DME synthesis on CZZ/H-FER from variable CO2/CO syngas feeds

Abstract: Catalyst systems for the conversion of synthesis gas, which are tolerant to fluctuating CO/CO2 gas compositions, have great potential for process-technical applications, related to the expected changes in the synthesis gas supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 61 publications
0
25
0
1
Order By: Relevance
“…Peláez et al 15 described the effects of different feed gas compositions on the process performance at a pressure of 30 bar. These and other works 7,[16][17][18][19] have shown that increasing CO 2 content in the feed decreases the process performance, and that water plays an important role, not only affecting the reaction kinetics, but also the catalyst structure by deactivation of the dehydration component g-Al 2 O 3 .…”
Section: Co 2 Content In the Synthesis Gasmentioning
confidence: 75%
See 1 more Smart Citation
“…Peláez et al 15 described the effects of different feed gas compositions on the process performance at a pressure of 30 bar. These and other works 7,[16][17][18][19] have shown that increasing CO 2 content in the feed decreases the process performance, and that water plays an important role, not only affecting the reaction kinetics, but also the catalyst structure by deactivation of the dehydration component g-Al 2 O 3 .…”
Section: Co 2 Content In the Synthesis Gasmentioning
confidence: 75%
“…Following the reduction procedure, the catalyst was conditioned until stable catalyst activity was achieved, in order to decouple the kinetic measurements from deactivation effects. The reduction and conditioning procedures are described in detail elsewhere 17 and summarized in the ESI. † The kinetic measurements were performed at a pressure of 50 bar under variation of the CZA-to-g-Al 2 O 3 weight ratio (m), temperature (T), space time (s), and carbon oxide ratio (COR), The experimental conditions as summarized in Table 2 were chosen in order to measure intrinsic kinetics i.e., by minimizing heat and mass transport limitations.…”
Section: Kinetic Measurementsmentioning
confidence: 99%
“…The temperature was measured at the outside of the reactor wall, details about the equipment are reported elsewhere. 37 Prior to the experiments, pre-catalysts were heated to 100 °C in Ar for 1 h. Catalyst reduction was performed by heating to 200 °C in 5% H 2 in Ar with a heating rate of 0.33 °C min −1 , followed first by increasing the H 2 content to 50% and then the temperature to 240 °C with a heating rate of 0.2 °C min −1 . These conditions were kept constant for 5 h. Every catalyst was tested at 50 bar, 230 °C and 250 °C, with two feed gas compositions (H 2 /N 2 /CO/CO 2 /Ar: 34 : 15 : 15 : 0 : 36 and 34 : 15 : 14 : 1 : 36, respectively) and gas hourly space velocity (GHSV) of 24 000 mL h −1 g −1 to ensure conversion in the kinetic region.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…Bei der direkten einstufigen Umsetzung von CO x /H 2 zu DME lässt sich der CO x -Umsatzgrad verglichen mit der reinen Methanolsynthese steigern. Hierzu werden die Cu-basierten Katalysatoren für die Methanolsynthese und saure Feststoffkatalysatoren für die Dehydratisierung zu DME in unterschiedlichen Katalysatorkombinationen 56) und Konfigurationen 57,58)…”
Section: Synthese Der Chemischen Energieträgerunclassified